Creating space for religious diversity at work - Gümüsay, A; Smets, M; Morris, T (Harvard Business School Publishing, 2020)
Accommodating highly diverse religious beliefs and practices within an organization is challenging, but possible. The authors describe the efforts of KT Bank — a firm whose leaders include Muslims, members of other faiths, and people without strong religious convictions — to accommodate and support all beliefs. Two methods stand out: The bank cultivated flexible messaging around their purpose that allowed different groups to interpret those communications in ways that were most meaningful to them, and it provided separate physical spaces and schedule flexibility for employees to be able to practice their faith while at work but away from their colleagues.